INTELLECTUAL CAPITAL APPROACH FOR A BETTER CORPORATE GOVERNANCE OF SHARIA BANKING - Purnomo, Hadi (IQTISHADIA, 2018)
AbstractThe Implementation of corporate governance of sharia banking in Indonesia has not been effective. Sharia banking in Indonesia do not yet have a standard of sharia governance framework as a guideline for the implementation of corporate governance. This study was conducted to analyze the implementation of corporate governance and intellectual capital condition of sharia banks, and to develop a more effective model of corporate governance by using the approach of intellectual capital. The data came from the annual financial statements of 12 Sharia Commercial Banks (BUS), and information based on answers to questionnaires by sharia banking practitioners. The results of this study indicate that the condition of intellectual capital contributes to the performance of BUS, while the implementation of corporate governance does not contribute significantly. However, corporate governance and intellectual capital contribute simultaneously to the performance of BUS. The implication based on finding indicated that intellectual capital can be developed as a basic for implementation of corporate governance in sharia banking. This is a new approach because the concept of corporate governance is generally more focused on rules and policies, it is rare to consider a holistic approach and align with the conditions of the company's intellectual capital.Keywords: corporate governance; intellectual capital; sharia commercial bank (BUS); sharia governance framework